If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x(x + 1) = 42 Reorder the terms: 3x(1 + x) = 42 (1 * 3x + x * 3x) = 42 (3x + 3x2) = 42 Solving 3x + 3x2 = 42 Solving for variable 'x'. Reorder the terms: -42 + 3x + 3x2 = 42 + -42 Combine like terms: 42 + -42 = 0 -42 + 3x + 3x2 = 0 Factor out the Greatest Common Factor (GCF), '3'. 3(-14 + x + x2) = 0 Ignore the factor 3.Subproblem 1
Set the factor '(-14 + x + x2)' equal to zero and attempt to solve: Simplifying -14 + x + x2 = 0 Solving -14 + x + x2 = 0 Begin completing the square. Move the constant term to the right: Add '14' to each side of the equation. -14 + x + 14 + x2 = 0 + 14 Reorder the terms: -14 + 14 + x + x2 = 0 + 14 Combine like terms: -14 + 14 = 0 0 + x + x2 = 0 + 14 x + x2 = 0 + 14 Combine like terms: 0 + 14 = 14 x + x2 = 14 The x term is x. Take half its coefficient (0.5). Square it (0.25) and add it to both sides. Add '0.25' to each side of the equation. x + 0.25 + x2 = 14 + 0.25 Reorder the terms: 0.25 + x + x2 = 14 + 0.25 Combine like terms: 14 + 0.25 = 14.25 0.25 + x + x2 = 14.25 Factor a perfect square on the left side: (x + 0.5)(x + 0.5) = 14.25 Calculate the square root of the right side: 3.774917218 Break this problem into two subproblems by setting (x + 0.5) equal to 3.774917218 and -3.774917218.Subproblem 1
x + 0.5 = 3.774917218 Simplifying x + 0.5 = 3.774917218 Reorder the terms: 0.5 + x = 3.774917218 Solving 0.5 + x = 3.774917218 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-0.5' to each side of the equation. 0.5 + -0.5 + x = 3.774917218 + -0.5 Combine like terms: 0.5 + -0.5 = 0.0 0.0 + x = 3.774917218 + -0.5 x = 3.774917218 + -0.5 Combine like terms: 3.774917218 + -0.5 = 3.274917218 x = 3.274917218 Simplifying x = 3.274917218Subproblem 2
x + 0.5 = -3.774917218 Simplifying x + 0.5 = -3.774917218 Reorder the terms: 0.5 + x = -3.774917218 Solving 0.5 + x = -3.774917218 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-0.5' to each side of the equation. 0.5 + -0.5 + x = -3.774917218 + -0.5 Combine like terms: 0.5 + -0.5 = 0.0 0.0 + x = -3.774917218 + -0.5 x = -3.774917218 + -0.5 Combine like terms: -3.774917218 + -0.5 = -4.274917218 x = -4.274917218 Simplifying x = -4.274917218Solution
The solution to the problem is based on the solutions from the subproblems. x = {3.274917218, -4.274917218}Solution
x = {3.274917218, -4.274917218}
| 5+3x=2+10x | | 30-7c=10c-4 | | 5+3x=2+6x | | 3/4x+26=18 | | 4x-5x^2/x | | 2x-3(1)=-7 | | 26-3/4x=18 | | 5-3x=84+6x | | 12+14=3*f | | 5-3x=4+6x | | 6-8(5-3x)=0 | | 52+g=45+11 | | 2-6x=4+8x | | 4(6x-7)=32x | | 2-6x=14+8x | | z-51/6=116/7 | | 37+s=80/2 | | 3y-12x=18 | | H=16t^2-180t | | 2-3x=4+10x | | (3+2-2-1)(4+-1+-3)= | | 2-3x=4+8x | | 420/d=30 | | 2-3x=14+8x | | 5-3x=14+4x | | (5e^2j)/(4+5j) | | 5-3x=14+8x | | 57+4m=0 | | 5-3x=10+8x | | 5-6x=10+8x | | 5-6x=10+6x | | 2(-9.5)-3(1)= |